Sharia Financial Literacy Analysis : Case Study of Traditional Market in Yogyakarta - Ririn Nopiah Nopiah; Yuli Utami (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
As population growth and financial market developments increase, understanding financial literacy becomes important in order to create a quality society on ability to plan and manage their finances well. This research aims to determine the Sharia financial literacy level on traditional market traders in Yogyakarta. This research aims to determine the level of Sharia financial literacy on traditional market traders in Yogyakarta. This research used primary data consisting of 22 traditional markets in Yogyakarta out of 100 respondents. The method used in this research is Chi-Square analysis and processed by SPSS 20.0 for the Windows program . There are four independent variables that were used such as gender, age, education and expenditure. Meanwhile, the dependent variable is Sharia financial literacy either in the knowledge or in the capability of the respondents. The results of the statistics test revealed that traditional market traders have a medium level of knowledge and capability in Sharia financial literacy. The variables of age, education and expenditure show that there are differences in the level of Sharia financial literacy. Meanwhile, the variable of gender showed there is no difference at this level among traditional market traders in the City of Yogyakarta.